2022
DOI: 10.1111/jcmm.17491
|View full text |Cite
|
Sign up to set email alerts
|

Kallistatin prevents ovarian hyperstimulation syndrome by regulating vascular leakage

Abstract: Angiogenesis and increased permeability are essential pathological basis for the development of ovarian hyperstimulation syndrome (OHSS). Kallistatin (KS) is an endogenous anti‐inflammatory and anti‐angiogenic factor that participates in a variety of diseases, but its role in OHSS remains unknown. In this study, treating a human ovarian granulosa‐like tumour cell line KGN and human primary granulosa cells (PGCs) with human chorionic gonadotropin (hCG) reduced the expression of KS, but increased the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Angiogenesis-related proteins are closely associated with the pathophysiology of OHSS 36 , 37 . EGR1 is a key regulator of angiogenesis 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis-related proteins are closely associated with the pathophysiology of OHSS 36 , 37 . EGR1 is a key regulator of angiogenesis 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Permeability assay was performed as previously described (Huang et al 2022 ). Briefly, mice were injected with 0.1 mL Evans blue (5 mM; MilliporeSigma, Merck, Darmstadt, Germany) through the caudal vein after anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, several cytokines and angiogenic molecules, including vascular endothelial growth factor (VEGF), have been involved in the pathogenesis of OHSS (Wang et al 2021 ). Previous studies indicated that the effective inhibition of the VEGF-related vascular permeability via targeting VEGF secretion could prevent the progression of OHSS (Hortu et al 2021 ; Huang et al 2022 ; Zhang et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%